Additive manufacture of PCL/nHA scaffolds reinforced with biodegradable continuous Fibers: Mechanical Properties, in-vitro degradation Profile, and cell study. (5th January 2022) - Hedayati, Seyyed Kaveh; Behravesh, Amir Hossein; Hasannia, Sadegh; Kordi, Omid; Pourghaumi, Majid; Saed, Arvin Bagheri; Gashtasbi, Fatemeh
Graphical abstract: Highlights: Scaffolds were FDM printed smultaneously with reinforced continuous bio-fibers. PGA suture yarn and nHA particles were both usedin various contents simultaneously. Evaluated mechanical properties showed an outstanding enhancements. Degradation profiles showed tunable properties for tissue engineering applications. Morphology and biological properties justified the obtained results. Abstract: In this study, an innovative method of "in-situ impregnation" was implemented in the Fused Deposition Modeling (FDM) process to produce poly (∊‐caprolactone) (PCL) scaffolds with enhanced mechanical and biological properties utilizing continuous biodegradable polyglycolic acid (PGA) suture yarns. The study aimed to introduce composite scaffolds, having a nominal porosity of 60% and 0°/60°/120° fibers layout, with tunable mechanical and biological properties for tissue engineering applications. Three different fiber volume contents (15, 25, and 35 vol%) were successfully embedded in the specimens during printing. To enhance the compressive properties, nano‐hydroxyapatite (nHA) was added to the PCL matrix in three levels (0, 10, and 20 wt%). Degradation behaviors of both tensile and compression specimens were also assessed in DMEM and Sörensen buffer. The biological properties of the scaffolds, including surface morphology, biocompatibility, and cell adhesion, were also evaluated. According to the results, incorporating the PGA fibers and nHA particles remarkably enhanced mechanical properties, degradation, and cell adhesion. Also, the composite scaffolds exhibited superior water uptake and hydrophilicity compared to the non-reinforced ones. The results suggest that the introduced 3D printed composite can be produced as a suitable material for bone tissue engineering and resorbable barrier membrane with the desired properties.